First data on Pterophoridae of Cambodia (Lepidoptera: Pterophoridae) - P. Ya. Ustjuzhanin; V. N. Kovtunovich (SHILAP, 2017)
We give first data on Pterophoridae of Cambodia. In previous publications, there was no indication of their habitat in Cambodia. Now we present 15 Pterophoridae species of 11 genera